The Effect of Increased Intracranial Pressure on Vestibular Evoked Myogenic Potentials in Superior Canal Dehiscence Syndrome - Janky, Kristen L. (Clin Neurophysiol, 2014)
OBJECTIVE: To determine if vestibular evoked myogenic potential (VEMP) responses change during inversion in patients with superior canal dehiscence syndrome (SCDS) compared to controls. METHODS: Sixteen subjects with SCDS (mean: 43, range 30–57 years) and 15 age-matched, healthy subjects (mean: 41, range 22–57 years) completed cervical VEMP (cVEMP) in response to air conduction click stimuli and ocular VEMP (oVEMP) in response to air conduction 500 Hz tone burst stimuli and midline tap stimulation. All VEMP testing was completed in semi-recumbent and inverted conditions. RESULTS: SCDS ears demonstrated significantly larger oVEMP peak-to-peak amplitudes in comparison to normal ears in semi-recumbency. While corrected cVEMP peak-to-peak amplitudes were larger in SCDS ears; this did not reach significance in our sample. Overall, there was not a differential change in o- or cVEMP amplitude with inversion between SCDS and normal subjects. CONCLUSIONS: Postural-induced changes in o- and cVEMP responses were measured in the steady state regardless of whether the labyrinth was intact or dehiscent. SIGNIFICANCE: VEMP responses are blunted during inversion. Although steady-state measurements of VEMPs during inversion do not increase diagnostic accuracy for SCDS, the findings suggest that inversion may provide more general insights into the equilibration of pressures between intracranial and intralabyrinthine fluids.